Well-Controlled Generation Process of Bimetallic Ag//Au Colloidal Nanoparticles by Non-Thermal Plasma DC Glow Discharge - Alwan, Alwan M.; Khamis, Raad A.; Abdallah, Shahad M. (Iraqi Journal of Science, 2019)
In this paper, an inexpensive, simple and well-accurate process of the generation of bimetallic silver Ag//gold Au core//shell is colloidal metal nanoparticles (MNPs). This is achieved via an atmospheric pressure non-thermal plasma glow discharge between two electrodes. One of these electrodes is a capillary tube placing over solution about (1 cm) that acts as the cathode, while the other electrode is a metal disk immersed in the solution and acts as an anode. Glow discharge process carried out at room temperature using a home-made cell with (6 KV) applied voltage and direct current (DC) about (1.8 mA) for different discharge periods. A wide range of bimetallic Ag//Au colloidal MNPs was rapidly synthesized as a result of non-thermal plasma formation between a capillary tube and the surface of AgNO3 solution for (5 min) and a mixture of AgNPs-HAuCl4 solution for (5, 10 and 15 min). Field emission scanning electron microscope (FE-SEM), transmission electron microscope (TEM) and X-ray diffraction were used to investigate the structural properties of the bimetallic Ag//Au colloidal MNPs. While optical properties were investigated using a UV-Vis spectrophotometer. Results show that the discharge time plays a crucial role in modifying the bimetallic nanoparticles properties such as grain size, surface area, and optical stability. Moreover, TEM and FE-SEM confirm the formation of Ag//Au core//shell structure with uniform sizes and shapes.